Hubungan Dukungan Sosial terhadap Pengelolaan Emosi Marah (Anger Management) pada Siswa Kelas X MAN 1 Kota Padang - Hidayati, Miskatul; Rahmadhani, Amalia; Effendi, Vevriyani; Iqbal, Muhammad; Hidayati, Izzanil (Lembaga Yasin AlSys, 2025)
The aim of this research is to reveal whether there is a relationship between social support and students' ability to manage anger, especially for class X students at MAN 1 Padang City. This research uses a quantitative approach with a correlational research design. The sample used was 186 students selected through random sampling techniques (random sampling). The research instrument is a questionnaire with a Likert scale. The data was analyzed using the product moment correlation technique. Based on the results of the analysis, no significant relationship was found between the level of social support and students' ability to control anger, with a correlation of 0.093 and a significance of 0.210. Most students have social support and the ability to manage angry emotions at a moderate level. These results emphasize the importance of awareness in building healthy social relationships to be more effective in managing negative emotions such as anger.